Synergistic effects of advanced oxidization reactions in a combination of TiO2 photocatalysis for hydrogen production and wastewater treatment applications - Demir, M. E.; Chehade, G.; Dincer, I; Yuzer, B.; Selcuk, H. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In this paper, the synergistic effects of advanced oxidization reactions in a combination of TiO2 photocatalysis are comparatively investigated for hydrogen production and wastewater treatment applications. An experimental study is conducted with a photoelectrochemical reactor under a UV-light source. TiO2 is selected as the photocatalyst due to the high corrosion resistant nature and ability to form hydroxyl radicals with the interaction with photons. The synergetic effects of advanced oxidization processes (AOPs) such as Fenton, Fenton-like, photocatalysis (TiO2/UV) and UV photolysis (H2O2/UV) are investigated individually and in a combination of each other. The Fenton type reagent in the reactor is formed by anodic sacrificial of stainless-steel electrode with the presence of H2O2. The influences of various parameters, including pH level, type of the electrode and electrolyte and the UV light, on the performance of the combined system are also investigated experimentally. The highest chemical oxygen demand (COD) removal efficiency is observed as 97.9% for the experimental condition which combines UV/TiO2, UV/H2O2 and photo-electro Fenton type processes. The maximum hydrogen production rate from the photoelectrolysis of wastewater is obtained as 7.0 mg/Wh for the experimental condition which has the highest rate of photo-electro Fenton type processes. The average enhancement with the presence of UV light on hydrogen production rates and COD removal efficiencies are further calculated to be 3% and 20%, respectively. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Photoelectrochemical process; Fenton reagent; Wastewater; Solar energy; ADVANCED OXIDATION PROCESSES; ELECTRO-FENTON; DEGRADATION; REMOVAL; ACID; REACTIVE-BLACK-5; UV/TIO2; REAGENT; REACTOR; Chemistry; Electrochemistry; Energy & Fuels